Korelasi Status Gizi dan Risiko Fraktur pada Lansia Menggunakan FRAX Score di RS Manembo-nembo Desember 2024-Januari 2023 - Kalitouw, Praysi Alicia Ferliana; Winaktu, Gracia JMT; Darmawan, Guntur (Jurnal MedScientiae, 2025)
Fractures in the elderly, especially hip fractures, are a serious health problem because they increase the risk of disability and death. Nutritional status is thought to play a role in fracture risk, but the relationship between the two is still unclear. This study aims to determine the correlation between nutritional status and fracture risk using the FRAX Score. This study used a cross-sectional design with 55 elderly people as a sample, selected using total sampling. Nutritional status was measured using Mid-Upper Arm Circumference (MUAC), while fracture risk was assessed using FRAX Score. Spearman correlation analysis showed a weak negative correlation between nutritional status and the risk of major fracture (r = -0.227; p = 0.096) which was not significant, but there was a significant negative correlation with the risk of hip fracture (r = -0.390; p = 0.003), meaning that the lower the nutritional status, the higher the risk of hip fracture. The conclusion of this study shows that nutritional status is associated with the risk of hip fracture, but not with overall major fracture. Further research with more sensitive methods and larger sample sizes is needed to confirm these results.